Perceived effects of teleworking on adaptive performance: A moderated mediation model of leadership effectiveness and negative affect - Taskan, B.; Junça-Silva, A.; Caetano, António (International Journal of Organizational Analysis, 2024)
Purpose - Drawing on the Conservation of Resources theory, we contend that individuals' perceptions of telework effects associate with their adaptive performance by shaping their negative emotional experiences, with perceived leadership effectiveness acting as a critical moderator in this relationship. Design/methodology/approach - A cross-sectional design was used, with data collected from a final sample of 209 teleworkers via an online survey. Findings - The results demonstrated a significant indirect effect of the perceived effects of teleworking on adaptive performance through negative affect. Furthermore, leadership effectiveness moderated the indirect effect, in a way that the indirect effect was only significant for those who had ineffective leaders and moderate effective leaders; so, the indirect effect was strengthened for those who had less effective leaders (versus effective leaders). Originality - This study examines the positive link between teleworking perceptions and adaptive performance through the reduction of negative affect, in line with the Conservation of Resources theory. Moreover, a reduction in negative emotions among employees during telework is associated with enhanced performance. Notably, the study reveals that leadership effectiveness moderates this connection as playing a crucial role in moderating these effects, particularly when leaders are perceived as less effective, offering insights for organizations considering telework strategies.